Properties of iterated norms in Nikol’skii-Besov type spaces with generalized smoothness - Ayele, Tsegaye G.; Abebe, Abraham N. (Eurasian Mathematical Journal, 2010)
In this paper we consider iterated norms of Nikol’skii-Besov type in the spaces Bϕθ(··· (Bϕθ(Lp(Ω)) ···) with generalized smoothness ϕ and study their properties.